HEPA filtration improves asthma control in children exposed to traffic‐related airborne particles. (8th December 2019) - James, Christine; Bernstein, David I.; Cox, Jennie; Ryan, Patrick; Wolfe, Christopher; Jandarov, Roman; Newman, Nicholas; Indugula, Reshmi; Reponen, Tiina
Abstract: Traffic‐related airborne particles are associated with asthma morbidity. The aim of this study was to assess the impact of a high‐efficiency particulate air (HEPA) filtration on the concentrations of traffic particles and the resultant effect on children with asthma. Forty‐three children with asthma were enrolled in this double‐blind, placebo‐controlled crossover design. A HEPA air cleaner or a placebo "dummy" was placed in participants' homes for four weeks, interrupted by a one‐month washout period, before crossing over to the other treatment arm for four weeks. Air sampling and health outcomes, including asthma control (ACQ) and quality of life (AQLQ) measures, were completed prior to and at the end of each treatment arm. Indoor concentrations of traffic particles were significantly reduced with the HEPA treatment but not with the "dummy" treatment. In participants with poorly controlled asthma and lower quality of life at baseline, ACQ and AQLQ scores were significantly improved (1.3 to 0.9, P = .003 and 4.9 to 5.5, P = .02, respectively) following the HEPA treatment. In this study, HEPA filtration is associated with improved clinical outcomes and quality of life measures in children with uncontrolled asthma.